2014
DOI: 10.1111/jsap.12190
|View full text |Cite
|
Sign up to set email alerts
|

Complete uterine prolapse without uterine mucosal eversion in a queen

Abstract: A five-year-old female cat weighing 3 kg was presented by the owner after noticing a large pink, bilobed mass protruding through the vulva during labour. The cat was in good condition, with appropriate lactation, and the newborn kittens were nursing normally. The uterus was not reverted or invaginated at examination, and there was rupture of the mesovarium, mesometrium and uterine-vaginal connection around the cervix. Manual reduction of the prolapsed uterus was not possible because of torn ligaments. A coelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…The exact cause of uterine prolapse is unknown in cats (3,7). It has been suggested that powerful uterine and abdominal contractions, excessive oxytocin stimulation, severe tenesmus, and uterine atony are predisposing factors of uterine prolapse (3,6). In contrast with Bigliardi et al (3) and Jutkowitz (6), the uterine prolapse in this case was thought to be due to prolonged parturition (8), dystocia (9), and repeated pregnancy (4).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The exact cause of uterine prolapse is unknown in cats (3,7). It has been suggested that powerful uterine and abdominal contractions, excessive oxytocin stimulation, severe tenesmus, and uterine atony are predisposing factors of uterine prolapse (3,6). In contrast with Bigliardi et al (3) and Jutkowitz (6), the uterine prolapse in this case was thought to be due to prolonged parturition (8), dystocia (9), and repeated pregnancy (4).…”
Section: Resultsmentioning
confidence: 85%
“…The exact cause of uterine prolapse is unknown in cats (3,7). It has been suggested that powerful uterine and abdominal contractions, excessive oxytocin stimulation, severe tenesmus, and uterine atony are predisposing factors of uterine prolapse (3,6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one case of uterine evisceration in a queen is described in the literature. 5 Rupture of the vaginal wall with evisceration of different organs (including, but not exclusively, the uterus) has been described in women, 6,7 and similar cases are reported in ewes 8 and dogs (intestines, bladder and uterus). 9–12 Both uterine prolapse and uterine evisceration may have similar presenting signs and only a careful inspection of the prolapsed/eviscerated organ allows for an accurate diagnosis.…”
Section: Introductionmentioning
confidence: 90%
“…A case of distal uterine rupture (near the vagina) that led to complete uterine prolapse (Bigliardi et al, 2014) was also reported. It has been observed that the rupture of parts of the uterus is asymptomatic in cat.…”
Section: Discussionmentioning
confidence: 99%